2013
DOI: 10.3329/bmjk.v45i1-2.13625
|View full text |Cite
|
Sign up to set email alerts
|

Indication and outcome of relaparotomy after caesarean section

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 7 publications
3
20
0
2
Order By: Relevance
“…Hemorrhage was in the form of PPH (56.36%) followed by rectus sheath hematoma (14.55%) and intraperitoneal hemorrhage (12.73%). 3 Study by Levin I et al showed major cause of relaparotomy to be intra-abdominal bleeding (50%) followed by uncontrolled post-partum hemorrhage (35.7%), bowel injury or infection (10.7%) , and abdominal wall bleeding (3.6%). 4 In study by Seal SL et al post-partum hemorrhage (42.4%) and rectus sheath hematoma (27.3%) were the leading causes for relaparotomy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hemorrhage was in the form of PPH (56.36%) followed by rectus sheath hematoma (14.55%) and intraperitoneal hemorrhage (12.73%). 3 Study by Levin I et al showed major cause of relaparotomy to be intra-abdominal bleeding (50%) followed by uncontrolled post-partum hemorrhage (35.7%), bowel injury or infection (10.7%) , and abdominal wall bleeding (3.6%). 4 In study by Seal SL et al post-partum hemorrhage (42.4%) and rectus sheath hematoma (27.3%) were the leading causes for relaparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Bleeding points on under surface of rectus sheath should always be checked and secured to prevent rectus sheath hematoma. 3 In case of cesarean section bleeding may be present along uterine incision especially at uterine angles due to loose knot or loose sutures. Proper hemostasis during repair of uterine incision should be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations